La dolarización de la economía del Ecuador: tres años después - Naranjo Chiriboga , Marco (2003)
In base of the economic crisis suttered by i: cuador, during the eighty and ninety years, and its worsening in 1999, this is an analysis of the causes that leads Ecuador to take the official dollarization as a global economic policy. This is a chronology of the application of the new monetary system, an analysis of the Central Bank functions in this kind of regime and, finally, an evaluation of the Ecuadorian economy performance in the first three years 0f application of the dollarization system.